Multiwavelength analysis of short GRB 201221D and its comparison with other high & low redshift short GRBs. Issue 1 (4th August 2022) - , Dimple; Misra, K; Kann, D A; Arun, K G; Ghosh, A; Gupta, R; Resmi, L; Agüí Fernández, J F; Thöne, C C; de Ugarte Postigo, A; Pandey, S B; Yadav, L
ABSTRACT: We present a detailed analysis of short GRB 201221D lying at redshift z = 1.045. We analyse the high-energy data of the burst and compare it with the sample of short gamma-ray bursts (SGRBs). The prompt emission characteristics are typical of those seen in the case of other SGRBs except for the peak energy ( E p ), which lies at the softer end (generally observed in the case of long bursts). We estimate the host galaxy properties by utilizing the Python -based software Prospector to fit the spectral energy distribution of the host. The burst lies at a high redshift relative to the SGRB sample with a median redshift of z = 0.47. We compare the burst characteristics with other SGRBs with known redshifts along with GRB 200826A (SGRB originated from a collapsar). A careful examination of the characteristics of SGRBs at different redshifts reveals that some of the SGRBs lying at high redshifts have properties similar to long GRBs indicating they might have originated from collapsars. Further study of these GRBs can help to explore the broad picture of progenitor systems of SGRBs.